EFL Teachers' Optimism and Commitment and Their Contribution to Students' Academic Success - Lu, Di (Frontiers in Psychology, 2021)
The present review study determines to scrutinize EFL teachers’ optimism and commitment and their contribution to students’ academic success. Academic optimism as a new construct is evolving from the examination on positive psychology (PP), societal principal, and communal school assets that affect the attainment and success of all learners. Also within the past decades, commitment has acknowledged a great level of consideration, principally in structural research. The straightforward perseverance of this review is to encompass the concept of academic optimism to individuals, that is, to hypothesize theoretical optimism and approve the efficacy of this paradigm at the instructor level in students’ academic success. According to the literature review, the definition of these constructs, namely teachers’ optimism and commitment, students’ academic success, and empirical studies in this domain are presented. In conclusion, the implications for teachers, school principals, teacher-trainers, and future researchers are presented, and new guidelines for further research are determined.